2014
DOI: 10.1111/bjh.12796
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of 15 children with juvenile myelomonocytic leukaemia who developed blast crisis: MDS Committee of Japanese Society of Paediatric Haematology/Oncology

Abstract: Summary Juvenile myelomonocytic leukaemia (JMML) is a rare haematopoietic stem cell disease of early childhood, which can progress to blast crisis in some children. A total of 153 children diagnosed with JMML were reported to the Myelodysplastic Syndrome Committee in Japan between 1989 and 2007; 15 of them (9·8%) had 20% or more blasts in the bone marrow (blast crisis) during the disease course. Blast crisis occurred during observation without therapy (n = 3) or with oral 6‐mercaptopurine treatment (n = 9) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…In the present case, blastic transformation occurred 1.5 years after diagnosis while the patient was still under oral 6‐MP therapy. Although our patient was successfully treated with systemic chemotherapy followed by HSCT, JMML in the blastic phase is known to be associated with high mortality . Therefore, it is expected that the mechanism and risk factors of blastic transformation will be clarified in the near future.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In the present case, blastic transformation occurred 1.5 years after diagnosis while the patient was still under oral 6‐MP therapy. Although our patient was successfully treated with systemic chemotherapy followed by HSCT, JMML in the blastic phase is known to be associated with high mortality . Therefore, it is expected that the mechanism and risk factors of blastic transformation will be clarified in the near future.…”
Section: Discussionmentioning
confidence: 93%
“…The clinical course of JMML is heterogeneous, ranging from spontaneous regression to a highly aggressive phenotype that requires timely hematopoietic stem cell transplantation (HSCT). Previous studies have reported several cases of JMML developing blastic transformation during an indolent clinical course, but the underlying mechanism of transformation has not been well understood . Here we report a case of JMML with blastic transformation caused by additional copy number gains (CNGs) of the KRAS mutant allele.…”
Section: Introductionmentioning
confidence: 89%
“…The finding of an aberrant B‐lymphoblast population was another unique feature for our patient. The blast phase of JMML is typically myeloid, similar to chronic myeloid leukemia (CML), though B‐ and T‐cell transformations have been reported . In CML, a minority of patients will have a small abnormal B‐lymphoblast population that does not necessarily signify impending progression to a B‐lymphoblastic phase .…”
Section: Discussionmentioning
confidence: 99%
“…It is known that JMML can progress to blast crisis (≥20% blasts in BM). In a Japanese study, Honda et al . reported that 15 (9.8%) of 153 patients with JMML had progressed to blast crisis, and Luna‐Fineman et al .…”
Section: Clinical Course and Risk Assessment Of Jmmlmentioning
confidence: 99%
“…found that an abnormal clone already existed in approximately 5% of BM cells at diagnosis in all the patients who initially possessed a normal karyotype but acquired chromosomal abnormalities 1–14 months after treatment with 6‐mercaptopurine (6MP). Moreover, Honda et al . reported that 12 of 15 patients with developing blast crisis had a normal karyotype at diagnosis, but that karyotypic abnormalities were detected in 10 of 15 children at the time of blast crisis.…”
Section: Clinical Course and Risk Assessment Of Jmmlmentioning
confidence: 99%